Microleakage of CEM cement in two different media - Ghorbani, Zahra; Kheirieh, Sanam; Shadman, Bahareh; Eghbal, Mohammad Jafar; Asgary, Saeed (Iranian Endodontic Journal, 2009)
INTRODUCTION: Sealing ability of root-end filling materials is of great importance. It can be investigated by measuring microleakage. The purpose of this in vitro study was to evaluate microleakage of calcium enriched mixture (CEM) cement in two different media including phosphate buffer solution (PBS) and distilled water. MATERIALS AND METHODS: Twenty single-rooted human teeth were selected. All teeth were root-end filled with CEM cement. Samples were divided into two groups of 10 each and were placed in PBS or distilled water. The microleakage was measured after 12 and 24 h, 14 and 30 days with Fluid Filtration device. Data were statistically analyzed by repeated measures test. RESULTS: Sealing ability of CEM cement was significantly superior in PBS compared to distilled water (P<0.05). This study also showed that time had no significant effect on the sealing ability of CEM cement. CONCLUSION: Media can significantly affect the microleakage of CEM cement. PBS can provide more phosphorous ions for hydroxyapatite formation of CEM cement; therefore, CEM cement can seal more effectively with PBS.